THE IMPLEMENTATION OF KG ENGLISH CLUB PROGRAM AS A FORM OF KOMPAS GRAMEDIA CORPORATE SOCIAL RESPONSIBILITY FOR CHILDREN - Dwi Haryanti; Indra Lestari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
As a company that is aspiring to enlighten the community through its various business networks, Kompas Gramedia has CSR activities series in the education sector with the title Education Inspirationâ€, where one of which is the KG English Club. This research aims to describe the implementation of the KG English Club program as a form of Kompas Gramedia Corporate Social Responsibility (CSR). This research used a qualitative approach with a descriptive method. Data collection techniques in this research were through in-depth interviews, documentation, and audio-visual materials. The results showed that the implementation form of the KG English Club program was corporate citizenship with cause branding method and community volunteering category. The stages of program implementation were conducted with CSR implementation framework which is plan, do, check, and improve. The driving factors in this program implementation were there is no English subject in the K-13 curriculum of Elementary School, there is some support of local residents and parents, the provision of adequate facilities, and collaboration with competent parties. The inhibiting factors in this program implementation were there is no person in charge of teachers in each class, a limited number of volunteers, and a delay in the implementation of the next period due to the covid-19 virus pandemic.